2008
DOI: 10.1007/s00262-008-0631-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor iNOS and COX-2 in stage III malignant cutaneous melanoma

Abstract: Our data show that iNOS is an independent and stronger prognostic factor for OS in stage III malignant cutaneous melanoma than COX-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
4
41
1
2
Order By: Relevance
“…This is in accordance with previous observations that COX-2 and its direct product PGE 2 are expressed at high levels in malignant melanomas and often correlate with poor prognosis (18,19). Interruption of the COX-2/PGE 2 pathway has been shown to be effective in blocking MDSCs induced by a mixture of cytokines in vitro (17,20).…”
Section: Introductionsupporting
confidence: 79%
“…This is in accordance with previous observations that COX-2 and its direct product PGE 2 are expressed at high levels in malignant melanomas and often correlate with poor prognosis (18,19). Interruption of the COX-2/PGE 2 pathway has been shown to be effective in blocking MDSCs induced by a mixture of cytokines in vitro (17,20).…”
Section: Introductionsupporting
confidence: 79%
“…In 2002, Cohen et al reported constitutive ERK-phosphorylation in >20% of benign nevi and >80% of primary melanoma (14), and hence confirmed activation of MAPK-signaling as an early event in human melanoma development. Pre-clinical studies developed over the following 15 years have underscored the importance of the BRAF-MAPK pathway in a multitude of processes involved in melanoma development and progression and BRAFV600E has been established as central for the control of melanoma cell proliferation and cell cycle progression, apoptosis, migration, invasion, glucose metabolism, adaptation to hypoxia or angiogenesis (3,(15)(16)(17)(18)(19)(20)(21)(22). Indeed it has now become well accepted that melanomas harboring BRAF mutations are addicted to the MAPK-pathway, as BRAFV600E cells show significant sensibility towards either genetic or chemical inhibition of this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the emerging pathogenic role of endogenous NO in the development and clinical course of melanoma. In fact, con stitutive expression of inducible form of iNOS correlates with poor survival (14)(15)(16). NO seems to initiate progression of human melanoma via a feedback loop mediated by apurinic/apyrimidinic endonuclease-1/ redox factor-1 (17).…”
Section: Introductionmentioning
confidence: 99%